2016
DOI: 10.1155/2016/1897039
|View full text |Cite
|
Sign up to set email alerts
|

Discharge against Medical Advice at Neonatal Intensive Care Unit in Gujarat, India

Abstract: Objective. We explored reasons for discharged against medical advice (DAMA) of neonates from a neonatal intensive care unit (NICU) through in-depth interviews of the parents/guardians. Methods. Of 456 babies admitted to NICU during April 2014 to March 2015, 116 babies were DAMA. Parents of randomly selected 50 babies of these 116, residing within 50 kilometers, were approached for in-depth interviews at their homes. Audio recordings were done and manually transcribed, analyzed in detail to explore common threa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 16 publications
6
31
0
Order By: Relevance
“…Most of the studies reported financial constraints as one of prominent reasons for requesting LAMA which is quite different in present study as treatment in SNCU is free of cost. 4,12,14 Self-discharge to take the neonate to a better equipped facility was the commonest reasons cited in the present study. This may be because of the impending fear of deterioration of the neonate and lack of a nearby referral centre with difficult roads and unavailability of vehicles at odd times which may impede timely referral as and when required.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Most of the studies reported financial constraints as one of prominent reasons for requesting LAMA which is quite different in present study as treatment in SNCU is free of cost. 4,12,14 Self-discharge to take the neonate to a better equipped facility was the commonest reasons cited in the present study. This may be because of the impending fear of deterioration of the neonate and lack of a nearby referral centre with difficult roads and unavailability of vehicles at odd times which may impede timely referral as and when required.…”
Section: Discussionmentioning
confidence: 80%
“…This study showed that sepsis and birth asphyxia were the common causes, this is corroborated by other studies. 4,8,11 Hatim in his study found transient tachypnea of neonates and suspected sepsis to be the common morbidities in neonates being taken LAMA.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is interesting to note the 10% rate of parents leaving the NICU with their infant against medical advice. A Saudi Arabian study demonstrated a rate of 1.6% [18], while a study in India showed a rate of 25.4% [19]. In the latter study, economic considerations were the most commonly indicated reason by parents, followed by lack of improvement and poor prognosis [19].…”
Section: Plos Onementioning
confidence: 88%
“…In addition, they also undergo financial and social turmoil. The attitudes of a poorly-adjusted family will definitely impact the treatment of the child with a congenital anomaly, and as often happens, they will likely be denied care since healthcare is mostly an out-of-pocket expense in India (20).…”
Section: Abortion and Down Syndromementioning
confidence: 99%